All superheroes need photo ops - Stephens, Elizabeth, 1991- (Stephens, Elizabeth, 1991- ; Supers in the city, 2025)
From the moment forty-eight alien superheroes crash-landed on Earth, photographer Monika Neumann had a favorite. She's been crushing on the literally electrifying Taranis ever since she saw the cutie crawling out of his pod. Unfortunately, his popularity isn't exactly crackling these days. He could use an image boost.Monika is in. One right photo op and she'll put her ridiculously hot lightning-bolt-wielding hero back in the public's favor. The best part is, the mission will bring her closer to Taranis. She's already looking forward to the sparks. Monika never imagined there'd be a worst part: an accidental recording that reveals Taranis could be more villain than hero. In fact, her pretty golden boy can get kind of ugly.Going all 007 and spying on Taranis isn't the adventure in romance and derring-do she expected. Can she trust him? Doubtful. Can she resist him? No way. Is she ready to risk everything on a shimmering Champion with the power to zap her heart in two? Well, yeah.